POLA PENGASUHAN DAN PENINGKATAN ASPEK PERKEMBANGAN PENGETAHUAN MORAL MELALUI GERAK DAN LAGU PADA ANAK USIA DINI - Dhaifi, Ilzam; Putri, Yayuk (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2023)
Moral development needs to be instilled from an early age, including awareness of gender differences. Moral instillation in children will hopefully have implications for their awareness and sensitivity about pro-social conditions that must be built properly. One of the actions of instilling moral education through music activities is movement and the song "touch is not allowed". The aims of the study were 1) to describe the implementation of movement and song activities in improving children's sexual moral education, 2) to find out the results of the development of sexual moral education in children. The research method used was Classroom Action Research (PTK) which was carried out in two cycles in Group A2 RA Mujahidin Sumberkima Bali. The research data was collected through observation techniques, documentation, and analysis of child development outcomes. The results of the study concluded that 1) activities to increase the knowledge of AUD sexual Moral Education through gestures and touching songs are not permitted by mentioning which limbs may be touched and which cannot be touched, singing and imitating movements and songs, touching is not permitted, 2) movement activities and songs are able increasing the development of children's sexual moral understanding in cycle 1 by 53% and increasing in cycle II by 92% and this shows the category of achieving the target of completeness. The results of this study indicate that knowledge of sexual moral education by practicing movements and songs has implications for increasing knowledge of sexual moral education in early childhood at this research location.